Determining the prognostic significance of IKKα in prostate cancer. Issue 14 (21st July 2020) - Montes, Melania; MacKenzie, Lewis; McAllister, Milly J.; Roseweir, Antonia; McCall, Pamela; Hatziieremia, Sophia; Underwood, Mark A.; Boyd, Marie; Paul, Andrew; Plevin, Robin; MacKay, Simon P.; Edwards, Joanne
Abstract: Background: As the survival of castration‐resistant prostate cancer (CRPC) remains poor, and the nuclear factor‐κB (NF‐κB) pathways play key roles in prostate cancer (PC) progression, several studies have focused on inhibiting the NF‐κB pathway through generating inhibitory κB kinase subunit α (IKKα) small molecule inhibitors. However, the identification of prognostic markers able to discriminate which patients could benefit from IKKα inhibitors is urgently required. The present study investigated the prognostic value of IKKα, IKKα phosphorylated at serine 180 (p‐IKKα S180) and threonine 23 (p‐IKKα T23), and their relationship with the androgen receptor (AR) and Ki67 proliferation index to predict patient outcome. Methods: A cohort of 115 patients with hormone‐naïve PC (HNPC) and CRPC specimens available were used to assess tumor cell expression of proteins within both the cytoplasm and the nucleus by immunohistochemistry. The expression levels were dichotomized (low vs high) to determine the associations between IKKα, AR, Ki67, and patients' I survival. In addition, an analysis was performed to assess potential IKKα associations with clinicopathological and inflammatory features, and potential IKKα correlations with other cancer pathways essential for CRPC growth. Results: High levels of cytoplasmic IKKα were associated with a higher cancer‐specific survival in HNPC patients with low AR expression (hazards ratio [HR], 0.33; 95% confidence interval [CI] log‐rank, 0.11‐0.98; P  = .04). Furthermore, nuclear IKKα (HR, 2.60; 95% CI, 1.27‐5.33; P  = .01) and cytoplasmic p‐IKKα S180 (HR, 2.10; 95% CI, 1.17‐3.76; P  = .01) were associated with a lower time to death from recurrence in patients with CRPC. In addition, high IKKα expression was associated with high levels of T‐cells (CD3+ P  = .01 and CD8+ P  = .03) in HNPC; however, under castration conditions, high IKKα expression was associated with high levels of CD68+ macrophages ( P  = .04), higher Gleason score ( P  = .01) and more prostate‐specific antigen concentration ( P  = .03). Finally, we identified crosstalk between IKKα and members of the canonical NF‐κB pathway in the nucleus of HNPC. Otherwise, IKKα phosphorylated by noncanonical NF‐κB and Akt pathways correlated with members of the canonical NF‐κB pathway in CRPC. Conclusion: The present study reports that patients with CRPC expressing high levels of nuclear IKKα or cytoplasmic p‐IKKα S180, which associated with a lower time to death from recurrence, may benefit from IKKα inhibitors.